2001
DOI: 10.1159/000047881
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular Disorders and Hormones in Women

Abstract: Temporomandibular disorders (TMD) are loosely defined as an assorted set of clinical conditions, characterized by pain and dysfunction of the masticatory system. Pain in the masticatory muscles, in the temporomandibular joint (TMJ), and in associated hard and soft tissues, limitation in jaw function, and sounds in the TMJ are common symptoms. That women make up the majority of patients treated for TMD is extensively hypothesized and documented in numerous epidemiological studies. Certain contradictory studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
180
0
21

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(223 citation statements)
references
References 19 publications
(24 reference statements)
11
180
0
21
Order By: Relevance
“…Also, TMD occurs more commonly in women (75-80%) than in men, which was confirmed in this study. The reason for this very high sex difference is unknown; probable reasons could be: biological and physiological, behavioural, and genetic differences (Warren and Fried, 2001). There are some musculoskeletal disorders with females outnumbering males, like fibromyalgia (Plesh and Gansky, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Also, TMD occurs more commonly in women (75-80%) than in men, which was confirmed in this study. The reason for this very high sex difference is unknown; probable reasons could be: biological and physiological, behavioural, and genetic differences (Warren and Fried, 2001). There are some musculoskeletal disorders with females outnumbering males, like fibromyalgia (Plesh and Gansky, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiological studies have reported that TMD is more prevalent in women than in men (Campbell et al, 1993;LeResche, 1997;Kapila and Xie, 1998), which suggests the involvement of sex hormones, such as estrogen, in the pathogenesis of this disease. Although estrogen is known to play important roles in the etiology of postmenopausal osteoarthrosis or rheumatoid arthritis in systemic joints (Ushiyama et al, 1995;Khalkhali-Ellis et al, 2000), little information has been available regarding the relationship between estrogen and the etiology of TMD (for review, see Warren and Fried, 2001).…”
mentioning
confidence: 99%
“…(29) ülkemizde yaptıkları prevalans çalışmasında TMEDS'nin kadınlarda daha fazla görüldüğünü bulmuştur. Kadın oranının yüksekliği, hormonal, psikolojik ve ergonomik nedenlerle açıklanmaya çalışıldığı gibi, kadınların daha fazla tedavi arayışında olmasına da bağlı olabilir (30). Çalışmamızda hastaların yaş ortalaması ve kadın erkek oranı üç farklı alt tanı grubuna göre bakıldığında farklılık göstermemektedir.…”
Section: Gereç Ve Yöntemunclassified